(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The cluster approach is effectively used to provide the population with quality agricultural products due to the formation of efficient high-tech and competitive agro-industrial production based on innovative development. Currently, the processes of integration based on the clustering of agriculture and processing industry are coming to the fore in the development of the agro-industrial complex. The article describes the need to organize agroclusters, its goals and tasks. Opinions were also given about the agrocluster, which operates in the cultivation, processing and sale of fruits and vegetables in Namangan region. Recommendations are given for the development of agroclusters in the regions.